GEOMETRIC MODELING AS A TOOL TO IMPROVE THE QUALITY OF GRAPHIC TRAINING OF STUDENTS - Evgeniya P. Aleksandrova; Konstantin G. Nosov; Irina D. Stolbova (Открытое образование (Москва))
The article discusses the potential use of modern computer technology in the framework of geometrical graphic training students at the Technical University. Examples of solving problems of geometric modeling based on the basic provisions of descriptive geometry and using instrumental possibilities of computer graphics.